2020
DOI: 10.3389/fcell.2020.00486
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors to Overcome Resistance to Targeted and Immuno Therapy in Metastatic Melanoma

Abstract: Therapies that target oncogenes and immune checkpoint molecules constitute a major group of treatments for metastatic melanoma. A mutation in BRAF (BRAF V600E) affects various signaling pathways, including mitogen activated protein kinase (MAPK) and PI3K/AKT/mammalian target of rapamycin (mTOR) in melanoma. Target-specific agents, such as MAPK inhibitors improve progression-free survival. However, BRAF V600E mutant melanomas treated with BRAF kinase inhibitors develop resistance. Immune checkpoint molecules, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 133 publications
(160 reference statements)
0
29
0
Order By: Relevance
“…In addition to its direct anticancer activity, HDACi has pleiotropic immunomodulatory effects (31)(32)(33). HDACi can enhance the intratumoral infiltration of CD8+ T cells and macrophages, decrease the intratumoral infiltration of T-regulatory cells, myeloid-derived suppressor cells, and protumorigenic M2 macrophages, induce the intratumoral expression of multiple chemokines, upregulate the expression of MHC and co-stimulatory molecules, enhance immune recognition, promote tumor-specific T cell-mediated killing of cancer cells, and sensitize tumor cells to NK cell lysis (32,(34)(35)(36)(37)(38)(39)(40)(41)(42). Preclinical studies have demonstrated that HDACi can enhance the anticancer activity of immunotherapy in several types of cancers (36,37,(43)(44)(45).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In addition to its direct anticancer activity, HDACi has pleiotropic immunomodulatory effects (31)(32)(33). HDACi can enhance the intratumoral infiltration of CD8+ T cells and macrophages, decrease the intratumoral infiltration of T-regulatory cells, myeloid-derived suppressor cells, and protumorigenic M2 macrophages, induce the intratumoral expression of multiple chemokines, upregulate the expression of MHC and co-stimulatory molecules, enhance immune recognition, promote tumor-specific T cell-mediated killing of cancer cells, and sensitize tumor cells to NK cell lysis (32,(34)(35)(36)(37)(38)(39)(40)(41)(42). Preclinical studies have demonstrated that HDACi can enhance the anticancer activity of immunotherapy in several types of cancers (36,37,(43)(44)(45).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The main difficulty in designing trials specifically for this patient population is that despite the increasing amount of information on possible resistance mechanisms we do-similar to the first-line decision-still lack established markers that would allow us to point out a specific resistance mech-anism for a therapeutic decision. Therefore, drugs like HDAC inhibitors that can target several resistance mechanisms at the same time [22] might at the moment be specifically interesting in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibition of specific signaling cascades in malignant cells often allows for collateral escape and continued function akin to the resistance mechanisms seen in BRAF inhibition [ 80 ], and thus, pleiotropic drugs may afford the potential for increased durability. Pro-neoplastic oncogenic driver targets involved in cell proliferation include phosphatidlyinositol-3-kinase (PI3K), bruton tyrosine kinase (BTK), MET proto-oncogene, and cyclin dependent kinases (CDKs), among many others [ 81 , 82 , 83 , 84 , 85 ]. While the plethora of oncogenic driver inhibitors act via varied mechanisms, ultimately, their targets include pathways which disrupt growth and replication (see above) or aberrant differentiation (e.g., the hedgehog pathway, cereblon, ATR3), allowing for increased drug efficacy in rapidly dividing tumor cells.…”
Section: Small Molecule Drugs and Potential Synergy With Immune Chmentioning
confidence: 99%